Increasing the lifetimes of charge separated states in porphyrin–fullerene polyads. Issue 35 (23rd August 2017) - Gao, Di; Aly, Shawkat M.; Karsenti, Paul-Ludovic; Brisard, Gessie; Harvey, Pierre D.
Abstract : The rate for electron transfer is (3 to 4) × 10 10 s −1 for the polyads [ZnP ]–□–[ZnP ]–C60 and [ZnP ]–□–[ZnP (C60 )]–□–[ZnP ] ([ZnP ] = zinc(ii )porphyrin, C60 = N -methyl-2-phenyl-3, 4-fulleropyrrolidine, □ = C6 H4 ––C6 H4 ) but the back transfer occurs in the ps and ns time scale whether the e − returns to the central or terminal [ZnP + ˙] unit. Abstract : Two linear polyads were designed using zinc(ii )porphyrin, [ZnP ], and N -methyl-2-phenyl-3, 4-fullero-pyrrolidine (C60 ) where C60 is dangling either at the terminal position of [ZnP ]–C6 H4 ––C6 H4 –[ZnP ]–C60 (1 ) or at the central position of [ZnP ]–C6 H4 ––C6 H4 –[ZnP (C60 )]–C6 H4 ––C6 H4 –[ZnP ] (2 ) in order to test whether the fact of having one or two side electron donors influences the rate of electron transfer, k et . These polyads were studied using cyclic voltammograms, DFT computations, steady state and time-resolved fluorescence spectroscopy, and femtosecond transient absorption spectroscopy (fs-TAS). Photo-induced electron transfer confirmed by the detection of the charge separated state [ZnP˙ + ]/C60 ˙ − from fs-TAS occurs with rates ( k et ) of 3–4 × 10 10 s −1 whereas the charge recombinations (CRs) are found to produce the [ZnP ] ground state via two pathways (central [ZnP˙ + ]/C60 ˙ − (ps) and terminal central [ZnP˙ + ]/C60 ˙ − (ns) producing [ 1 ZnP ] (ground state) and [ 3 ZnP* ]). The formation of the T1 species is more predominant for2 .